Debating American Identity : Southwestern Statehood and Mexican Immigration. - Noel, Linda C., 1966- (University of Arizona Press, 2014)
"Debating American Identity is an innovative look at four national debates over the inclusion of the Mexican-origin population in the United States in the early twentieth century. Linda C. Noel explores different conceptions of American identity through disputes over Arizona and New Mexico statehood, temporary workers, immigration, and repatriation"--